DAMPAK DARI MENULIS JURNAL DALAM MENINGKATKAN KEMAMPUAN MENULIS SISWA KELAS SATU SMA BABUSSALAM PEKANBARU - Alkhair, Nadia; ', Afrianto; Delfi, Syofia (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study was aimed at finding out the effect of journal writing on enhancing the writing skill of the first year students of SMA Babussalam Pekanbaru. It was an experimental research with one pre-post test design. A single group was chosen to be the sample of this study by cluster random sampling to get a treatment. There were 24 students joined this study as experimental group. A writing test was used both in pre and post-test. In order to know the difference between pre and post-test and to analyze the hypotheses, t-test was used. After analyzing the data, it was found out that t-test score was 5.74 while t-table score was 2.069. Since t-test was higher than t-table, it can be concluded that alternative hypothesis was accepted. It can be further understood that ‘There is significant effect of journal writing on enhancing the writing skill of the first year students of SMA Babussalam Pekanbaru’. Based on research findings, it is suggested that the students can write their journals for several months so the results will be better.